2024
DOI: 10.3390/ijms25020962
|View full text |Cite
|
Sign up to set email alerts
|

PAMPs and DAMPs in Sepsis: A Review of Their Molecular Features and Potential Clinical Implications

Sara Cicchinelli,
Giulia Pignataro,
Stefania Gemma
et al.

Abstract: Sepsis is a serious organ dysfunction caused by a dysregulated immune host reaction to a pathogen. The innate immunity is programmed to react immediately to conserved molecules, released by the pathogens (PAMPs), and the host (DAMPs). We aimed to review the molecular mechanisms of the early phases of sepsis, focusing on PAMPs, DAMPs, and their related pathways, to identify potential biomarkers. We included studies published in English and searched on PubMed® and Cochrane®. After a detailed discussion on the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 233 publications
0
3
0
Order By: Relevance
“…Secondly, very low MOIs such as this do not stimulate early cytokine responses ex vivo because they are often rapidly cleared. Thirdly, there is now good evidence that PAMPs and DAMPs may not only be associated with live bacteria but also in soluble forms not associated with bacteria [60,61]. Fourth, viable bacteria are counted in cfu/mL, but many studies also quantify genome copies/mL using nucleic acid amplification techniques [62].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, very low MOIs such as this do not stimulate early cytokine responses ex vivo because they are often rapidly cleared. Thirdly, there is now good evidence that PAMPs and DAMPs may not only be associated with live bacteria but also in soluble forms not associated with bacteria [60,61]. Fourth, viable bacteria are counted in cfu/mL, but many studies also quantify genome copies/mL using nucleic acid amplification techniques [62].…”
Section: Discussionmentioning
confidence: 99%
“…TLRs, the main exponents of the PPR (Pattern Recognition Receptor) family, detect pathogens and damaged cells through pathogen- and damage-associated molecular patterns (PAMPs and DAMPs). They are expressed on immune cells and their activation results in the secretion of pro-inflammatory cytokines (including IL-1, IL-6, IL-8, TNF, IL-33, and IFN-γ) [ 64 , 65 ] and in the regulation of the balance between Th1 and Th2 immune responses [ 66 ]. Beside their pro-inflammatory role, some studies have suggested that TLR2 and TLR4 are also involved in EMT through the modulation of the TGF-β pathway [ 67 ].…”
Section: The Role Of Immune Dysregulation In Driving Epithelial-to-me...mentioning
confidence: 99%
“…In the extracellular environment, ATP functions as one of the damage-associated molecular patterns (DAMPs), in which elevated concentration leads to the activation of immune system cells and the production of pro-inflammatory cytokines and factors [ 185 ]. Also, ATP stimulation of MSCs results in the secretion of various enzymes and factors, including COX-2, IDO, and iNOS, which stimulate the pro-inflammatory activity of the immune system [ 186 , 187 ].…”
Section: Role Of Mesenchymal Stem Cells In Asd Treatmentmentioning
confidence: 99%